Utilizing an interpersonal communication framework to understand information behaviors involved in HIV disclosure. Issue 4 (August 2017) - Li, Jo-Yun; Qiao, Shan; Harrison, Sayward; Li, Xiaoming
Highlights: An interpersonal communication conceptual diagram of HIV disclosure is proposed. Examining antecedents of disclosure using interpersonal communication theories. Adding medicating mechanisms "uncertainty" and "information behaviors" to disclosure process. Proposing mediating effects of information management to HIV disclosure process. Abstract: Psychological factors have been widely used in existing empirical studies to understand individuals' decisions regarding HIV disclosure. However, limited studies have examined disclosure by applying a comprehensive interpersonal communication framework to understand information behaviors relevant to disclosing one's HIV status, including seeking information and sharing information. Thus the mediating role of information flow and its relationship with disclosure uncertainty for those living with HIV have been largely overlooked. We propose an integrated conceptual framework to connect the antecedent factors of disclosure decision-making, the potential route of the disclosure process, and the consequences of disclosure through integrating components from key interpersonal communication theories including the theory of communication privacy management and social influence theory and adding mediating mechanisms of "uncertainty" and "information behaviors." Applying interpersonal communication theory and a comprehensive information management model to HIV disclosure may offer novel opportunities to support individuals living with HIV through the development of theory-based disclosure interventions to facilitate this complicated but critical process.